Epidemiological profile of pacients undergoing mastectomy after diagnosis of breast cancer (Research, Society and Development, 2024)
Breast cancer is the most common type of neoplasm in women in Brazil apart from non-melanoma skin tumors. Many times, the diagnosis is made late, and the patient is in a more advanced stage of the disease requiring invasive surgical treatments, such as mastectomy. The study aims to define the epidemiological profile of patients undergoing mastectomy after being diagnosed with breast cancer. It was analyzed gender, age group, type of surgery performed, quantity of each type of surgery, result of breast histology, histological grade, and reconstructive surgeries from 2013 to 2023. The data was collected through the DATASUS and SISCAN database, in addition to being tabulated and analyzed in a Microsoft Excel spreadsheet. Finally, it was concluded that the profile of patients undergoing mastectomy are middle-aged women with high histological grade.